Electrical properties of boron doped CVD diamond after plasma cleaning probed by capacitance-voltage profiling - Araujo, Luana S.; Berengue, Olivia [UNESP]; Baldan, Maurício; Ferreira, Neidenei; Moro, Joaõ; Chiquito, Adenilson (Springer Nature, 2014)
Doped diamond films grown by chemical vapor techniques has been used to study hydrogen and oxygen terminated diamond. It is known that the electrical characteristics of metal-diamond interface are strongly affected by the diamond surface features. O2 plasma treatment was used as a cleaning procedure for as grown diamond samples leading to changes in the capacitance measurements after treatment. The alteration in the characteristics of the samples can be attributed to the surface adsorbates like hydrogen and water vapor present in the atmosphere. The results indicates that the O2 plasma treatment was effective in cleaning the surface revealing the expected features of a p-type diamond film.
Keywords: Diamond; surface reaction; thin film